THOUGHTS ON THE RESPONSIBILITY OF LEGAL ENTITIES IN EUROPE - Dimitris Liakopoulos (Diponegoro Law Review, 2020)
The present work is concentrated on a construction of a legal person's model responsibility for the EU countries, with a particular attention for a comparative analyse of the systems assumed in certain European nations (Italian, France, Spain, German, Belgian systems). The end result of this system is oriented to corporates responsibilities that, after the mass transfer of general interest from public service to privates services, corporates have to attend to relatives guarantees. Because it was established  a social insecurity level, we have produced a model of corporation’s organisation engaged of a security position, that exceed the traditional standard of culpability.